2009
DOI: 10.7150/ijms.6.258
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of proximal femur infections with antibiotic-loaded cement spacers

Abstract: In case of periprosthetic hip infections the implantation of antibiotic-loaded PMMA spacers is accepted for an adequate treatment option. Although their indication for the treatment of destructive, bacterial infections of the proximal femur would make sense, literature data are scarce. Hence, the aim of this study was to evaluate the efficacy of antibiotic-impregnated spacers in the treatment of proximal femur infections.In 10 consecutive patients (5 M/ 5 F, mean age 66 y.) with bacterial proximal femur infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 16 publications
0
29
0
4
Order By: Relevance
“…Na le ży rów nież wspo mnieć o wy bo rze me to dy le cze nia. Ogól nie przy ję tym le cze niem jest dwu etapo wa en do pro te zo pla sty ka re wi zyj na z za sto so waniem spa ce ra lub in ne go "wy peł nia cza" sta wu, który w od po wied nio dłu gim cza sie wy dzie li miej sco wo du żą ilość an ty bio ty ku [1,6,7,10]. Jed no eta po wa rewi zja koń czą ca się usu nię ciem pro te zy bez po nowne go za bie gu jest za re zer wo wa na dla wy jąt ko wych sy tu acji.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Na le ży rów nież wspo mnieć o wy bo rze me to dy le cze nia. Ogól nie przy ję tym le cze niem jest dwu etapo wa en do pro te zo pla sty ka re wi zyj na z za sto so waniem spa ce ra lub in ne go "wy peł nia cza" sta wu, który w od po wied nio dłu gim cza sie wy dzie li miej sco wo du żą ilość an ty bio ty ku [1,6,7,10]. Jed no eta po wa rewi zja koń czą ca się usu nię ciem pro te zy bez po nowne go za bie gu jest za re zer wo wa na dla wy jąt ko wych sy tu acji.…”
Section: Discussionunclassified
“…Obec nie naj lep szym roz wią za niem dla cho rych z IOP wy da je się być dwu eta po wa re im plan ta cja sztuczne go sta wu [1,6,7]. Pierw szy za bieg ope ra cyj ny po le ga na usu nię ciu en do pro te zy, oczysz cze niu za ka żo nej ko ści i usu nię ciu oko ło pro te zo wych tka nek mar twych (de bride ment lo ży pro te zy).…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Of 9 hips, 8 were successfully converted to THA after an average of 23 weeks. Kelm et al 13 reported the efficacy of antibiotic-loaded spacers in the treatment of proximal femur infections in 8 patients with bacterial proximal femur infections. The spacer was produced using a CAD (computer aided design)-planned and CNC (Computer numerical control)-milled 2-part mold of polyoxymethylene, but cement acetabulum was not performed in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…11 In another report, TNP required a mean period of 9 days, ranging from 3 to 16 days, until the inflammatory parameters of C-reactive protein, erythrocyte sedimentation rate and, leucocyte blood count had normalized and wound secretion had markedly decreased. 12 In retrospect, the total duration of 4 weeks of TNP and irrigation as used in the current case could probably have been shortened.…”
Section: Discussionmentioning
confidence: 99%